46 Alternative strategies to childhood fontan completion and consequences for multi-organ function. (22nd February 2018) - Adhvaryu, K; Carruthers, L; Jansen, K; Hudson, M; O'Sullivan, J; Crossland, D; Hasan, A; Coats, L
Abstract : Purpose: Occasionally, single ventricle (SV) patients survive into adulthood without Fontan palliation; with the theoretical advantage of potentially lower inferior caval vein pressures. We studied liver and renal function in an adult cohort of SV patients who had not undergone Fontan completion (F-) and a group who had Fontan completion (F+) in adult life. Methods: Retrospective case note analysis between 1990–2017. Results: There were 12 SV patients in the F- group [9 (75%) male, age 41 years (18–52), 8 (67%) had previous surgery, aortopulmonary shunt: 3, Glenn: 5]. Outcomes: 2 deaths (at 42 and 24 years), 1 assessed for transplant, 2 for TCPC completion, 7 balanced circulations. At last review, saturations were 78% (69–85), Hb 192 g/L (159–252), creatinine 88 μmol/L (59–129), eGFR 65 (59– >90), albumin 46 g/L (35–50), bilirubin 20 μmol/L (12–46) and platelets 220 (105–333). Abdominal USS was available in 5: normal liver (2), mild-moderate fibrosis (2), cirrhosis (1). There were 8 SV patients in the F+ group, [3 (37%) male, age 46 years (23–55), age at Fontan completion 28 years (16–46)]. Follow-up was 13 years (2–24). Outcomes: 1 transplant, 4 failing Fontan physiology, 3 well. At last review, saturations were 95% (75–96), Hb 163 g/L (108–171), creatinine 76 μmol/L (66–148), eGFR 72 (36– >90), albumin 47 g/L (30–52), bilirubin 13 μmol/L (10–39) and platelets 216 (137–429). Abdominal USS was available in 5: normal liver (2), mild-moderate fibrosis (2), severe fibrosis (1). Conclusion: In both groups, synthetic liver function was preserved and a minority showed advanced fibrosis/cirrhosis on USS. Renal function was impaired, more prominently in the non-Fontan group, likely reflecting the effect of chronic hypoxia. Strategies to delay or avoid Fontan completion may not preserve liver function.